Corporate Social Responsibility, Investor Behaviors, and Stock Market Returns: Evidence from a Natural Experiment in China - Wang, Maobin; Qiu, Chun; Kong, Dongmin (2011)
This article studies how financial investors respond to firms’ corporate social responsibility (CSR) performance in terms of their investing behaviors, and how such behaviors change contingent on an event that provokes their attention and concerns to CSR. Using the melamine contamination incident in China as a natural experiment, it is found that neither the individual investors’ nor the institutional investors’ behaviors are influenced by firms’ CSR performance before the incident. Nevertheless, in the post-event period, institutional investors’ behaviors are significantly influenced by firms’ CSR performance that exceeds a certain threshold. Furthermore, such an effect diminishes for a better CSR performance. In comparison, the authors do not find any effects of CSR performance on individual investors, either before the event or after the event. Finally, firms’ performance and investors’ behaviors jointly affect firms’ stock returns after the event but not before the event. This article reconciles the mixed findings in the literature on the effect of firms’ CSR performance on their financial performance by showing that such an effect exists in a contingent manner. Furthermore, the authors show that a too low or a too high CSR performance could lead to undesirable responses from investors. Therefore, managers should pay attention to optimizing firms’ CSR activities.
Keywords: Chinese stock market; Emerging markets; investors’ behaviors; Event Study; stock markets; Financial Performance; Corporate Social Responsibility